Sinkronisasi Kebijakan Pemerintah Pusat dan Daerah dalam Penanganan Kemiskinan Ekstrem - Wahyudi Akhmad Albarqi; Aminullah Aminullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Extreme poverty represents a complex, multidimensional challenge in development that demands cohesive policy integration among various governmental tiers. The Indonesian government has established goals to expedite the eradication of extreme poverty via diverse national frameworks and initiatives, yet their success hinges on the extent of alignment between central and regional policies in areas such as strategic planning, financial allocation, and program execution. This research seeks to examine the patterns of policy alignment between central and local authorities, pinpoint the obstacles encountered during execution, and develop recommendations for enhancing collaborative efforts in tackling extreme poverty. Employing a qualitative descriptive methodology, data collection involved reviewing policy documents and development plans, complemented by discussions with relevant stakeholders at the regional level. The outcomes reveal that efforts toward policy synchronization have been made by merging national and local planning frameworks and initiatives, although persistent issues persist, such as inconsistencies in poverty statistics, jurisdictional overlaps among sectors, and inadequate inter-institutional cooperation. These insights imply that effective reduction of extreme poverty necessitates reinforced strategies for policy alignment, unified data platforms, and the adoption of cross-level and cross-sector partnership models to guarantee that measures are precisely directed, enduring, and impactful in diminishing the population affected by extreme poverty.